1998
DOI: 10.1063/1.476478
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of pure Lb1 fluorescence from redshifted indole-polar solvent complexes in a supersonic jet

Abstract: Two-photon polarized fluorescence excitation and vibronically resolved one-photon dispersed fluorescence spectra of the long-wavelength absorbing van der Waals complexes of indole with water, methanol, and formamide were examined for the purpose of firmly assigning the nature of the lowest singlet excited electronic state. The two-photon spectra for all of these complexes have circular/linear polarization ratios of absorptivity (Ω-values) that show that excitation is to the Lb1 state. Analysis of the Franck–Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…The female natural sex hormone estradiol and amino acids tryptophan as part of protein chain are applicable in pharmaceutics and as fluorescent detectors in different biological objects. Fluorescent properties of tryptophan are controlled by the indole chromophore center and strongly depend on chemical and spatial structure of environment 30, 31. The tryptophan cage miniprotein is under consideration also as one of the realistic samples and appropriate for applying the hybrid technique of CIS and elongation methods.…”
Section: Computational Details and Methodologymentioning
confidence: 99%
“…The female natural sex hormone estradiol and amino acids tryptophan as part of protein chain are applicable in pharmaceutics and as fluorescent detectors in different biological objects. Fluorescent properties of tryptophan are controlled by the indole chromophore center and strongly depend on chemical and spatial structure of environment 30, 31. The tryptophan cage miniprotein is under consideration also as one of the realistic samples and appropriate for applying the hybrid technique of CIS and elongation methods.…”
Section: Computational Details and Methodologymentioning
confidence: 99%
“…Whereas the 1 L b state behaves similarly to the ground electronic state, the 1 L a energy depends strongly on the solvent. These effects have been probed using microsolvation in van-der-Waals clusters using vibrationally 10,[18][19][20][21] and rotationally resolved spectroscopy. [22][23][24] From Stark effect measurements the dipole moment of indole-water in its ground and first excited electronic state was determined and a significant change of the water molecules' orientation upon excitation was observed.…”
Section: Introductionmentioning
confidence: 99%
“…þ measured via the vibrationless intermediate state S 1 , 0 0 of the cluster at 35099 cm À1 (Hager et al, 1985;Tubergen & Levy, 1991;Braun, Grebner, & Neusser, 1998;Helm et al, 1998;Short & Callis, 1998) is shown in the middle trace of Figure 11. We identify intramolecular modes in the (indole Á H 2 O) þ spectrum by a comparison with the indole þ MATI spectrum.…”
Section: B Matimentioning
confidence: 99%